Assessing service quality at the University of Malaya Library - Kaur, K. (University of Malaya Library, 2008)
Service quality and customer satisfaction are rapidly evolving areas in library and information science research. Service quality measures from the marketing literature are being effectively used by library science researchers to develop library service quality measuring tools. This paper describes the results of a study which examines the perceptions of the academic staff on the quality of University of Malaya Library services. It also attempts to assess the impact of that service on academic staff's work and their perceived level of satisfaction towards the library services. The survey instrument was a questionnaire adopted from a quality impact survey based on SERVQUAL dimensions. Results revealed that academic staff perceive the quality of library services to be just above average. The library staff are considered quite helpful and are able to instill confidence in library users. Academic staff also believe that the library has a positive impact on their teaching, learning and research. The overall satisfaction with the library services received a satisfactory rating. Based on the results, one has to conclude that even though the quality of library service is perceived as just above average, academics will.